PEGARUH KEADILAN, SISTEM PERPAJAKAN, DISKRIMINASI, KEMUNGKINAN TERDETEKSI KECURANGAN DAN INTENSITAS PEMERIKSAAN PAJAK TERHADAP PERSEPSI WAJIB PAJAK MENGENAI ETIKAPENGGELAPAN PAJAK (Studi Empiris Pada Kantor Pelayanan Pajak Pratama Bangkinang) - Muhammad Ammar; Desmiyawati Desmiyawati; Devi Safitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this research is to analyze Influence of Fairness, Tax System, Discrimination, Possibility of Fraud Detected, and Intensity of Tax Audit on the perception of tax payer on the ethics of tax evasion. The sample consists of 100taxpayers listed in the Tax Office of Pratama Bangkinang. The data that was used in this research was primary data and selected by using accidental sampling method, while the data processing methods used by research are the multiple regression analysis use SPSS version 22.00 as the software for processing the data.The result of the adjusted R-square showed that the value of the adjusted Rsquare is 0,721, which mean that 72.1% the ethics of tax evasion can be explain by the variation of the independent variables, while the other 27,9% explained by other variables which not included in this research. Results of hypothesis testing showed,the result indicate that fairness has affected the perception of taxpayer on the ethics of tax evasion. Tax system has affected the ethics of tax evasion, discrimination has affected the ethics of tax evasion, possibility of fraud detected has affected the ethics of tax evasion, and intensity of tax audit has affected the ethics of tax evasion.Keyword: fairness, tax,discrimination, fraud, and audit